Near normalization of peripheral blood markers in HIV-infected patients on long-term suppressive antiretroviral therapy: a case–control study. (1st November 2020) - Brochado-Kith, Oscar; Martinez, Isidoro; Berenguer, Juan; Medrano, Luz Maria; González-García, Juan; Garcia-Broncano, Pilar; Jiménez-Sousa, María Ángeles; Carrero, Ana; Hontañón, Victor; Muñoz-Fernández, María Ángeles; Fernández-Rodríguez, Amanda; Resino, Salvador
Abstract : Objective: To explore the differences in peripheral blood markers between HIV well controlled patients on long-term suppressive antiretroviral therapy (HIV-group) and age-matched healthy controls, to evaluate the benefits of virological suppression in those patients. Methods: We performed a case–control study in 22 individuals in the HIV-group and 14 in the healthy control-group. RNA-seq analysis was performed from peripheral blood mononuclear cells. Peripheral blood T-cell subsets were evaluated by flow cytometry and plasma biomarkers by immunoassays. All P values were corrected by the false discovery rate ( q values). Results: Only the serine/arginine repetitive matrix 4 gene, which is involved in alternative RNA splicing events, was differentially expressed between HIV and healthy control groups ( q value ⩽0.05 and fold-change ≥2). However, 147 differentially expressed genes were found with a more relaxed threshold ( P value ⩽0.05 and fold-change ≥1.5), of which 67 genes with values of variable importance in projection at least one were selected for pathway analysis. We found that six ribosomal genes represented significant ribosome-related pathways, all of them downregulated in the HIV-group, which may be a strategy to facilitate viral production. T cells subset and plasma biomarkers did not show significant differences after false discovery rate correction ( q value >0.05), but a noncorrected analysis showed higher values of regulatory CD4 + T cells (CD4 + CD25 + CD127 −/low ), MCP-1, and sVEGF-R1 in the HIV-group ( P value ⩽0.05). Conclusion: T-cell subsets, plasma biomarkers, and gene expression were close to normalization in HIV-infected patients on long-term suppressive combination antiretroviral therapy compared with healthy controls. However, residual alterations remain, mainly at the gene expression, which still reveals the impact of HIV infection in these patients. Abstract : Supplemental Digital Content is available in the text